ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA SMA PADA MATERI BARISAK DAN DERET ARITMATIKA - Sri Kamulian; Syahriani Sirait; Ely Syafitri (Universitas Asahan, 2022)
AbstrakThis study aims to determine the ability of students mathematical representation on arithmetic sequences and series. This type of research is a qualitative approach. The research subjects were 15 students of class XI MIA 1 SMA Negeri 1 Air Batu T.A 2020/2021. The test instrument used in this study was in the form of 5 test questions referring to indicators of representational ability including: (1)visual representation ability, (2)mathematical expression representation ability, (3)written representation ability. Based on the results of the study, it was concluded that about 73% of students were able to work on visual representation ability questions and about 27% were less able to work on visual representation problems. While mathematical expression skills, about 53% of students were able to work on mathematical expression representation skills and about 47% were less able to work on mathematical expression representation problems. And for written text abilities, about 33% of students were able to work on written text representation abilities, and about 67% more who have not been able to work on written text representation problems. Keywords: Sequences and Series, Mathematical Representation Ability. AbtrakPenelitian ini bertujuan untuk mengetahui kemampuan representasi matematis siswa pada materi barisan dan deret aritmatika. Jenis penelitian ini adalah pendekatan kualitatif. Subyek penelitian adalah 15 siswa kelas XI MIA 1 SMA Negeri 1 Air Batu T.A 2020/2021. Instrumen tes yang digunakan dalam penelitian berupa 5 tes soal yang mengacu pada indikator kemampuan representasi diantaranya: (1)kemampuan representasi visual, (2)kemampuan representasi ekspresi matematis, (3)kemampuan representasi tertulis. Berdasarkan hasil penelitian diperoleh kesimpulan bahwa sekitar 73% siswa mampu mengerjakan soal kemampuan representasi visual dan sekitar 27% lagi yang kurang mampu mengerjakan soal representasi visual. Sedangkan kemampuan ekspresi matematis, sekitar 53% siswa mampu mengerjakan soal kemampuan representasi ekspresi matematis dan sekitar 47% lagi yang kurang mampu mengerjakan soal representasi ekspresi matematis. Dan untuk kemampuan teks tertulis, sekitar 33% siswa mampu mengerjakan soal kemampuan representasi teks tertulis dan sekitar 67% lagi yang belum mampu mengerjakan soal representasi teks tertulis.